Effects of Chronological Age, Relative Age, and Maturation Status on Accumulated Training Load and Perceived Exertion in Young Sub-Elite Football Players - Teixeira, José Eduardo; Alves, Ana Ruivo; Ferraz, Ricardo; Forte, Pedro; Leal, Miguel; Ribeiro, Joana; Silva, António J.; Barbosa, Tiago M.; Monteiro, António M. (Frontiers in Physiology, 2022)
The aims of this study were: (i) to analyse the influence of chronical age, relative age and biological maturation on accumulated training load and perceived exertion in sub-elite young football players and (ii) to understand the interaction effects amongst age grouping, maturation status and birth quartiles on accumulated training load and perceived exertion in this target population. A 6-week period (18 training sessions and 324 observation cases) concerning 60 young male sub-elite football players grouped into relative age (Q1 to Q4), age-group (U15, U17 and U19) and maturation status (Pre-PHV, Mid-PHV and Post-PHV). External training load was collected using 18Hz global positioning system technology (GPS), heart-rate measures by 1 Hz short-range telemetry system and perceived exertion with total quality recovery (TQR) and rating of perceived exertion (RPE). U17 players and U15 players have 2.35 (95% CI: 1.25–4.51) and 1.60 (95% CI: 0.19–4.33) more likely to pertain to Q1 and Q3, respectively. Negative magnitude for odds ratio was found in all four quartile comparison within maturation status (95% CI: -6.72–0.64), except for Mid-PHV on Q2 (95% CI: 0.19–4.33). Between- and within-subject analysis reported significant differences in all variables on age group comparison measures (F = 0.439 to 26.636, p = 0.000 to 0.019, η2 = 0.003 to 0.037), except for dynamic stress load (DSL). Between-subject analysis on maturity status comparison demonstrated significant differences for all training load measures (F = 6.593 to 14.424, p = 0.000 to 0.037, η2 = 0.020 to 0.092). Interaction effects were found for Age Group x Maturity Band x Relative Age (Λ Pillai’s = 0.391, Λ Wilk’s = 0.609, F = 11.385, p = 0.000, η2 = 0.391) and Maturity Band x Relative Age (Λ Pillai’s = 0.252, Λ Wilk’s = 0.769, F = 0.955, p = 0.004, η2 = 0.112). Current research has confirmed the effects of chronological age, relative age and biological maturation on accumulated training load. Perceived exertion does not seem to show any differences concerning age group or maturity status. Evidence should be helpful for professionals to optimize the training process and young football players’ performance.